Juvenile granulosa cell tumor of the ovary: A rare cause of precocious puberty in a toddler - Koodat, Amila Salih K; Joseph, Susy; Bindu, S (Indian Journal of Case Reports, 2024)
Ovarian tumors are a rare cause of sexual precocity in female children. Functional neoplasms of the ovary are relatively infrequent, and only 5% occur before puberty. Although ovarian juvenile granulosa cell tumor (GCT) is a rare tumor described infrequently in pediatrics, the most common presentation of this tumor is precocious puberty. We report a 1⅟2 year-old girl with isosexual precocious puberty, who presented with a rapid onset of premature menarche, pubic hair, and vaginal bleeding, with an abdominal mass on clinical examination. Ultrasonography of the pelvis and abdomen showed a heterogeneously hypoechoic solid mass with cystic areas and internal vascularity. The child underwent a left oophorectomy. Microscopic features of the resected mass were characteristic of juvenile GCTs. Even though the most common cause of precocious puberty in girls is idiopathic, functional ovarian tumors must be considered, especially when the onset is at an early age and puberty is rapidly progressive. Early-stage disease has a good prognosis, and adjuvant chemotherapy is not indicated.